2020
DOI: 10.3855/jidc.11449
|View full text |Cite
|
Sign up to set email alerts
|

Fungal osteomyelitis and soft tissue infections: Simple solutions to uncommon scenarios

Abstract: Introduction: Fungal osteoarticular/soft tissue infections (FOaSI) are an uncommon entity with protracted course due to variability in clinical picture, slow progression; resulting in misdiagnosis with empirical therapy. Recent studies have shown an alarming emergence of FOaSI in immunocompetent individuals with high mortality rates. This study recommends a protocol for managing these complex and confusing scenarios. Methodology: We have retrospectively analysed patients with FOaSI between January 2014 a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 13 publications
0
5
0
Order By: Relevance
“…The use of antifungal impregnated depot materials, removal of hardware, and irrigation may be indicated. The literature has shown that despite intense debridement, recurrence may occur 19 .…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…The use of antifungal impregnated depot materials, removal of hardware, and irrigation may be indicated. The literature has shown that despite intense debridement, recurrence may occur 19 .…”
Section: Discussionmentioning
confidence: 99%
“…F ungal infections of the musculoskeletal system are rare, but when present, they typically follow a chronic, low grade, persistent course 18,19 . A high level of suspicion and identification of the causal agent is a very important factor.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations